2017
DOI: 10.1080/07294360.2017.1303454
|View full text |Cite
|
Sign up to set email alerts
|

Do pictures ‘tell’ a thousand words in lectures? How lecturers vocalise photographs in their presentations

Abstract: This article explores how 145 photographs collected from 20PowerPoint lectures in undergraduate psychology at 16 UK universities were integrated with lecturers' speech. Little is currently known about how lecturers refer to the distinct types of photographs included in their presentations. Findings show that only 48 photographs (33%) included in presentation slides were referred to explicitly by exploring their features to make a point related to the lecture content, with only 14 of these used to invite studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…the dialogue stemming from educational research, philosophy and pedagogy-the move towards more integrative approach to artefacts is further based on the fact that: (i)n the last two decades, the global movements of multimodality (Jewitt, Bezemer and O'Halloran 2016;Iedema 2003;Jewitt, Kress, Ogborn and Tsatsarelis 2001;van Leeuwen 1998), new literacies (Freebody and Luke 1990;Knobel and Lankasher 2006;Lankshear and Knobel 2007) and multiliteracies (Anstey and Bull 2006;Cope and Kalantzis 2000;New London Group 1996) have been paving the way for renewed understanding of communication and education processes, especially in relation to technology mediation. (Lacković 2018) Such renewed understanding means that those processes include but go beyond language, bringing to higher education research and teaching the artefacts that surround us and are a part of us (Lacković 2018;Hallewell and Lacković 2017;Lacković 2010). As Susi (2006Susi ( : 2110 argues, 'one of the fundamental findings of cognitive science is that artefacts shape cognition and collaboration (Woods 1998)', building on the Russian cultural-historical school in psychology of the late 1960s and 1970s (Vygotsky 1978).…”
Section: Artefact Mediation and Multimodal Postdigital Dialogue (Nataša)mentioning
confidence: 99%
“…the dialogue stemming from educational research, philosophy and pedagogy-the move towards more integrative approach to artefacts is further based on the fact that: (i)n the last two decades, the global movements of multimodality (Jewitt, Bezemer and O'Halloran 2016;Iedema 2003;Jewitt, Kress, Ogborn and Tsatsarelis 2001;van Leeuwen 1998), new literacies (Freebody and Luke 1990;Knobel and Lankasher 2006;Lankshear and Knobel 2007) and multiliteracies (Anstey and Bull 2006;Cope and Kalantzis 2000;New London Group 1996) have been paving the way for renewed understanding of communication and education processes, especially in relation to technology mediation. (Lacković 2018) Such renewed understanding means that those processes include but go beyond language, bringing to higher education research and teaching the artefacts that surround us and are a part of us (Lacković 2018;Hallewell and Lacković 2017;Lacković 2010). As Susi (2006Susi ( : 2110 argues, 'one of the fundamental findings of cognitive science is that artefacts shape cognition and collaboration (Woods 1998)', building on the Russian cultural-historical school in psychology of the late 1960s and 1970s (Vygotsky 1978).…”
Section: Artefact Mediation and Multimodal Postdigital Dialogue (Nataša)mentioning
confidence: 99%
“…In the study of psychology lectures, little critical questioning of the photos used was found: a disturbing finding since meaning-making is based partially on "the socio-cultural conditioning surrounding the photograph: who it is viewed by, presented by, created by, where and why is it produced, who are the agents who have intentions and power (Hodge & Kress, 1988)?" (Hallewell & Lackovic, 2017). Our insistence on using blurred photos is to invite an exploration of the semiotic potential of these repetitive film frames, and provoke further critical reflection via our engagement with images in conversation.…”
Section: Communicating With Imagesmentioning
confidence: 99%
“…Therefore, we looked further but found very little research on how photos are used in higher education. Hallewell and Lackovic (2017) researching lecturing practices, pointed toward Posser and Roth (2003) who used a taxonomy of four functions for using photos: decorative, illustrative, explanatory and complementary and who revealed that "the semiotic potential of photographs in lectures is underused" (p. 13), suggesting that higher education practitioners could benefit from training in this regard. In the study of psychology lectures, little critical questioning of the photos used was found: a disturbing finding since meaning-making is based partially on "the socio-cultural conditioning surrounding the photograph: who it is viewed by, presented by, created by, where and why is it produced, who are the agents who have intentions and power (Hodge & Kress, 1988)?"…”
Section: Communicating With Imagesmentioning
confidence: 99%
“…Presentational software such as PowerPoint, which is a commonly used slideware, allows for the incorporation of images although critics argue that such these are sometimes only used for decoration (Gabriel, 2008) rather than being used in creative ways to enhance learning. Hallewell and Lackovic (2017) for example, explored the ways in which 145 photographs used in PowerPoint presentations were used in 16 UK universities for undergraduate Psychology lectures and found that only 33% were referred to explicitly with the majority representing a case of 'unprobed representations', that is, the photograph and its meaning were not explicitly referenced. Furthermore, Carpenter, Witherby and Tauber (2020) argue that students have a tendency to over-endorse the effectiveness of images even when they are only used for decorative purposes leading to them thinking they have learned more than they actually have.…”
Section: Introductionmentioning
confidence: 99%